Search for Transpace: A Study of Mohsin Hamid’s Exit West - Sukheeja, Vandana; Kaur Bhangu, Jap Preet (International Journal of English Literature and Social Sciences (IJELS), 2023)
The problem of refugees has spread at a large scale throughout the world in the twenty-first century. Refugees are the migrants worst-hit by their destinies as they are forced to leave their home and hearth due to some sort of political or religious conflicts, war or violence. They are completely unwanted in the country of their arrival due to fear and suspicion of the natives. At the same time refugees earnestly desire to be treated on humanitarian ground and regain the lost space in this world. Mohsin Hamid marvelously deals with this problem of refugees in his fourth novel Exit West (2017) from the transcultural lens with the hope to create a transpace for refugees. The paper examines how migrants are forced to leave their homeland as they are not considered as lawful citizen of the land and are devoid of basic human needs. The paper explores the struggle of refugees in the initial period before achieving their transcultural space in the foreign land. In addition to this, the paper also analyzes the effect of their movement, struggle and success in creating transpace on their identity.